Psychological effects of the COVID-19 outbreak on nurses working in tertiary women's and children's hospitals from Sichuan, China: A cross-sectional study - He, Qiuyang (Int J Disaster Risk Reduct, 2021)
The evolving COVID-19 pandemic is placing unprecedented pressures on health systems. Accumulative studies suggest that nurses were more likely to develop negative psychiatric outcomes following a public health disaster than other medical staffs, due to their more frequent and closer contact with patients. We examined the psychological status of nurses working in the tertiary women's and children's hospitals in Sichuan, China, in order to explore the possible effect of the COVID-19. The cross-sectional survey was conducted at the peak period of COVID-19 among 1971 nurses. Their anxiety, depression and self-efficacy were assessed by the seven-item anxiety scale (GAD-7), the nine-item Patient Health Questionnaire (PHQ-9), and the General Self-efficacy Scale (GSES), respectively. 1934 valid questionnaires were returned with a response rate of 98.1%. We found that 29.3% and 22.7% of the nurses were identified with anxiety and depressive symptoms, respectively. The median score of GSES was 30, which was at the upper middle level among all populations. Nurses having longer working years and cold-like symptoms, those who were at work during breakout period and working in pediatric ward were significantly associated with the presence of anxiety and depression. Findings suggest that the epidemic of COVID-19 does not necessarily affect the psychological health of nurses working in women's and children's hospitals in Sichuan. The results of this study could serve as valuable suggestions to direct the promotion of psychological well-being among targeted nurses.